Non-Cognitive Factors Affecting the Academic Performance of Fourth Year College Students of a Private College in Manila - Maria Pamela Magpily; Joseph Mercado (Athens Institute for Education and Research, 2015)
The paper explored the relationships between general weighted average (GWA) and type of parents' employment and educational attainment, type of family structure, study habits, nutrition, and extracurricular activities of fourth year college students aged 19-20. Using a stratified random sample, the population was divided into subpopulations or strata. Findings showed that a higher GWA was associated with length of study before break, regular supper intake, frequency of exercise, weekend activity, and extracurricular activities. The findings suggest that frequent breaks during study time, regular supper intake, participating in extracurricular activities in school, boosting level of exercise, and arranging a weekend activity may sharpen college students' performance in school. The significant finding of a positive link between regular supper intake and academic performance in college students is something new and surprising given the importance that most literature place on eating breakfast to start the day. Apparently, the relationship between regular supper intake and academic performance in university students has received little attention from practitioners and researchers in the field of education.